Regulation of Glutamine Synthetase by Light and during Nitrogen Deficiency in Synchronous Chlorella sorokiniana - Tischner, Rudolf (1980)
A method is described to achieve density labeling of proteins in unicellular algae by using (13)CO(2). This is a satisfactory procedure especially for work on nitrogen metabolism. The increase in activity of glutamine synthetase (EC 6.3.1.2.) and glutamate synthase (EC 1.4.7.1.) in Chlorella sorokiniana mediated by a dark/light shift and by nitrogen starvation were investigated. Using the method of density labeling and isopycnic centrifugation, we demonstrated that the increase in enzyme activity after a dark/light shift is based on activation rather than de novo synthesis. The increase in enzyme activity after transfer to nitrogen-deficient medium is based both on activation and de novo synthesis.